Gaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Agama Islam - Upe, Asrizal A.; Sukandar, Ahmad; Setiawan, Marwan (CV. Media Publikasi Profesional, 2021)
Human nature is a social creature which according to Aristotle is called the